The critical success factors of an education franchise. - Thien, Qi Yun. (2010)
Education has always been the key in the growth and development of Singapore, particularly in the years following 1965 when it became an independent republic. This is equally true for all developing countries. More so now in the 21st century, where the knowledge-based economy has become the main economic driver, education has become even more critical in shaping a country's future. Education may be pursued through different avenues such as public government schools, private schools and through non main-stream avenues such as franchised education centres. There has always been an interest in this large market by various stakeholders, particularly entrepreneurs who have emerged as founders of education centres that have expanded through franchising. This study focuses on primary and secondary education franchises. Most of these founders are also owners of the education franchises. With so many education organisations being set up, the question then is how to ensure the survival and success of the education franchise. As there is a lack of research in this area, especially in the local context, this research attempts to shed light on what makes an education franchise successful. A qualitative approach comprising extensive literature review and interviews with industry professionals was undertaken for this research. This report focuses on identifying the critical success factors of an education franchise.